Copolymerisation at work: The first example of a highly porous MOF comprising a triarylborane-based linker - Helten, Stella; Sahoo, Basudev; Bon, Volodymyr; Senkovska, Irena; Kaskel, Stefan; Glorius, Frank (CrystEngComm, 2015)
Two novel porous materials, namely, Zn4O(TPB)4/3(BDC) and chiral Zn4O(TPB)4/3(chir-BDC), have been synthesised by copolymerisation of the newly developed triarylborane linker 4,4′4″-boranetriyltris(3,5-dimethylbenzoic acid) (H3TPB) with the linear 1,4-benzenedicarboxylic acid (H2BDC) and chir-H2BDC, respectively. The compounds adopt ith-d topology and are microporous. The BET surface area of Zn4O(TPB)4/3(BDC) determined from the nitrogen adsorption isotherm measured at 77 K is 2874 m2 g-1 and both frameworks are accessible to organic dye molecules, the largest being Rhodamine B. Thus, the two compounds are the first examples of non-interpenetrated, highly accessible metal-organic frameworks comprising a triarylborane linker. The framework shows an enhanced isosteric heat of CO2 adsorption in comparison to the isoreticular DUT-6 compound.
CRIS-Team Scopus Importer:2023-03-20